State aid and the functioning of the Single European Market — the crisis perspective - Podsiado, Piotr (Ekonomia i Prawo. Economics and Law, 2016)
Motivation: The financial crisis and the collapsing of the financial market as a result of bankruptcy in 2008 of Lehman Brothers bank became the justification for the need for State intervention in order to prevent the bankruptcy of other financial institutions and related consequences for the real economy. Results: Essential in this range was the position of the European Commission, whose task is to exercise control over compliance with European rules relating to the Member States intervention in the economy. A special role is played here by rules on granting State aid because their violation can lead to distortions of competition in the Single European Market. Aim: The aim of the article is to analyze the conditions of admissibility of State aid in the European Union, taking into account the rules applicable to the aid for undertakings during the crisis.